Laparoscopic versus open inguinal hernia repair in infants: an initial experience. Issue 10 (5th August 2022) - Leng, Samantha; Jackson, Tracy; Houlton, Adelene; Dumitriu, Elisabeth; Pacilli, Maurizio; Nataraja, Ramesh
Abstract: Background: Inguinal hernia repair is a common operation performed in children. In Australia, open repair (OR) continues to be the preferred method of treatment in infants, despite laparoscopic repair (LR) gaining popularity amongst some international centres. Our aim was to analyse initial outcomes with LR at our paediatric centre. Methods: We conducted a retrospective review of all patients <1 year of age who received LR or OR between January 2017 and July 2021 at our institution. Data were retrieved from both electronic and scanned medical records. Data were analysed using an unpaired t ‐test, Mann–Whitney test, Fisher's exact test or simple linear regression. A P ‐value <0.05 was considered significant. Results: A total of 376 patients were identified: LR was performed in 73 patients, and OR in 303 patients. Bilateral repair was more common amongst patients receiving LR: 56.2% versus 21.5%, P = 0.0001, treating either a symptomatic hernia or an intra‐operative contralateral inguinal defect (70%). All LR patients received general anaesthetic, compared to 82.8% of patients in the OR group, P = 0.0001. There were no recurrences following LR and 3 with OR ( P = 1.0). The metachronous contralateral inguinal hernia rate following OR was 10% (21/206). There was no significant difference in other complications, including wound infection, haematoma, testicular atrophy, and hydrocele formation. Conclusion: In our population OR was performed more often than LR. Operative complication rates were equivalent between OR and LR groups. However, infants that underwent OR were significantly more likely to develop a MCIH . Abstract : Amongst Australian infants, the open approach to inguinal hernia repair is more common than laparoscopic repair. We analysed outcomes from both operative techniques at our tertiary paediatric institution. Open and laparoscopic inguinal hernia repairs produced the same complication rates in infants.